Recycling method of lithium battery positive electrode material
By using ternary melting salt materials to heat up the positive electrode material of waste lithium -ion battery, the problem of difficulty in the separation of adhesives in traditional recycling technologies has been solved, and high -efficiency and environmentally friendly positive electrode materials are recovered. Protection effect.
Patent Information
- Application Number
- CN202411324124.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-28
AI Technical Summary
Existing lithium battery positive electrode material recycling technology is difficult to completely separate the binder, resulting in complex and costly recycling processes, and traditional methods pose a threat to the environment and human health.
Mixing the three-yuan melting salt material (consisting of lithium nitrate, lithium hydroxide and lithium carbonate, the quality ratio is 3: (1.5-2.5): (0.25-1)) mix with the orthopedic material of the waste lithium-ion battery, which is separated from the heat treatment and is separated from the positive pole. Materials and sets to remove adhesives and supplement lithium.
The recycling of positive materials with low temperature, short -term, environmentally friendly, and high separation efficiency has been achieved, reducing toxic gas pollution, protecting the environment, simplifying the recycling process, and increasing economic benefits.
Smart Images

Figure CN119381607A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for recovering positive electrode materials of a lithium battery, belonging to the technical field of batteries. Background Art
[0002] Reasonable and effective recycling of S-LIBs has become an urgent task to alleviate the constraints of the industrial chain and environmental protection. The cathode material is the most critical component in S-LIBs, as it accounts for 40% of the cost of LIBs. At the same time, the cathode material is also the key to determining the performance of LIBs, such as energy density, safety, and cycle life. Therefore, it is urgent to achieve environmentally friendly and efficient separation of cathode materials and foil in the cathode to promote the healthy development of the S-LIBs recycling industry.
[0003] At present, the recycling technologies of nickel-cobalt-manganese ternary cathode materials (NCM) include pyrometallurgical technology, hydrometallurgical technology, pyrometallurgical-hydrometallurgical combined technology, biotechnology, direct regeneration and electrochemical recycling, among which hydrometallurgy is the most commonly used method. After adopting hydrometallurgical technology, a mixed solution of nickel, cobalt and manganese is obtained by sufficient extraction and sufficient reflux. If the mixed solution is further separated and purified, the cost will be very high and the process chain will be very long. Moreover, polyvinylidene fluoride (PVDF) is a common organic binder in pole pieces. Traditional wet recycling will cause the PVDF therein to be unable to be eliminated during the treatment of the pressureless cleaning system. The waste cathode material obtained still contains PVDF, and the foil and the cathode material are not easy to be completely peeled off, which increases the workload of the subsequent recycling process.
[0004] In order to achieve efficient separation of aluminum foil and cathode materials, people have also explored a variety of methods, including mechanical separation, alkaline dissolution, high-temperature calcination, organic solvent dissolution, and low-temperature solvent dissolution. Mechanical separation usually causes aluminum scrap residue hazards in the subsequent recycling process of waste cathode materials; the NaOH alkaline method dissolves aluminum foil, the separation steps are cumbersome, and a large amount of alkaline waste liquid is produced; calcination at a high temperature of 400-600°C with air, argon or oxygen can easily destroy the crystal structure of the waste cathode material and cause hydrogen fluoride to volatilize; PVDF solvents will produce a large amount of organic wastewater after being dissolved by NMP, DMF, DMAC, etc., posing a threat to humans and the environment.
[0005] Therefore, it is still necessary to find a new method to separate and treat organic binders with greener and more suitable reagents and to separate cathode materials and current collectors from S-LIBs, while achieving the regeneration of spent cathode materials. Summary of the invention
[0006] To solve the above problems, the present invention provides a method for recycling NCM positive electrode materials in waste lithium-ion batteries. This method overcomes the defect that the traditional method cannot completely separate the binder, and realizes the removal of the binder and the supplementation of lithium elements in one step. The battery prepared with the recycled material achieves improved electrochemical performance.
[0007] An object of the present invention is to provide a method for recycling positive electrode materials and current collectors of lithium batteries, comprising the following steps:
[0008] S1. Discharge waste lithium-ion batteries (S-LIBs), disassemble and collect positive electrode sheets;
[0009] S2, mixing the positive electrode plate with the ternary molten salt material, heating to a preset temperature for heat treatment to separate the positive electrode material of the lithium battery and the current collector, and recovering the positive electrode material of the lithium battery and the current collector;
[0010] The positive electrode material of the waste lithium-ion battery is a mixture of a nickel-cobalt-manganese ternary material and a conductive agent, the ternary molten salt material is composed of lithium nitrate, lithium hydroxide and lithium carbonate, and the mass ratio of the lithium nitrate, lithium hydroxide and lithium carbonate is 3: (1.5-2.5): (0.25-1); the preset temperature is greater than or equal to 200° C., and the heat treatment time is greater than or equal to 10 minutes.
[0011] Furthermore, in the nickel-cobalt-manganese ternary material, the molar ratio of Ni, Co and Mn is (8-9.5): (0.2-0.8): (0.2-0.8), such as NCM9055 and NCM8866. Most preferably, the nickel-cobalt-manganese ternary material is NCM9055.
[0012] Furthermore, the preset temperature is 350-500°C.
[0013] Furthermore, the heating is performed at a heating rate of 2-6°C / min.
[0014] Furthermore, the heat treatment time is 10-30 minutes.
[0015] Furthermore, LiNO3, LiOH, and Li2CO3 in the ternary molten salt material are mixed in a mass ratio of 3:(1.5-2.5):(0.25-1), for example, 3:1.5:0.25, 3:1.5:0.5, 3:1.5:0.75, 3:1.5:1, 3:2:0.25, 3:2:0.3, 3:2:0.35, 3:2:0.4, 3:2:0.45, 3: 2:0.5, 3:2:0.55, 3:2:0.6, 3:2:0.65, 3:2:0.7, 3:2:0.75, 3:2:0.8, 3:2:0.85, 3:2:0.9, 3:2:0.95, 3:2:1, 3:2.5:0.25, 3:2.5:0.5, 3:2.5:0.75, 3:2.5:1, etc., including but not limited to the proportions listed above.
[0016] Furthermore, the mass ratio of the ternary molten salt material to the positive electrode plate is (1-10): 1. For example, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, etc., including but not limited to the ratios listed above.
[0017] Further, the preset temperature may be 200-500°C, such as 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, and 340°C, preferably 350-500°C, for example 401°C, 402°C, 403°C, 404°C, 405°C, 406°C, 407°C, 408°C, 409°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C, 500°C, etc., including but not limited to the temperatures listed above.
[0018] Furthermore, the heat treatment time is 10-30 min, for example, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc., including but not limited to the time lengths listed above.
[0019] Furthermore, the heating rate is 2-6°C / min, such as 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, etc., including but not limited to the rates listed above.
[0020] Furthermore, the positive electrode material of the lithium battery is a mixture of a nickel-cobalt-manganese ternary material and a conductive agent;
[0021] Preferably, in the lithium battery positive electrode material, the mass percentages of the nickel-cobalt-manganese ternary material and the conductive agent are: 75-95% of the nickel-cobalt-manganese ternary material and 5-15% of the conductive agent;
[0022] Preferably, the conductive agent is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0023] Furthermore, the step S2 further includes a waste gas treatment step; the waste gas treatment is: passing the waste gas into an alkaline solution.
[0024] Furthermore, in the step S2, after the lithium battery positive electrode material and the current collector are separated, the lithium battery positive electrode material and / or the current collector are washed and dried to recover the lithium battery positive electrode material and / or the current collector.
[0025] Furthermore, after washing and drying the positive electrode material of the lithium battery, the method includes a step of crushing the positive electrode material of the lithium battery.
[0026] Furthermore, the pulverizing method includes air flow pulverizing.
[0027] Furthermore, the particle size D50 of the lithium battery positive electrode material after crushing is 1-10 μm.
[0028] The present invention claims protection for the lithium battery positive electrode material obtained by the above-mentioned recycling method.
[0029] Another object of the present invention is to provide a positive electrode plate, comprising a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer comprises the above recycled lithium battery positive electrode material (including a conductive agent) and a binder.
[0030] Further, the positive electrode active layer comprises the following components by mass percentage: 85-95% of lithium battery positive electrode material and 5-15% of binder. Wherein, the positive electrode active layer comprises the following components by mass percentage: 75-95% of NCM material, 5-15% of conductive agent and 5-15% of binder.
[0031] The present invention also provides a method for preparing the positive electrode sheet as described above, comprising the following steps:
[0032] S01, preparing a positive electrode active slurry by mixing a formulated amount of positive electrode material and a binder;
[0033] S02, coating the positive electrode active slurry on at least one side of the current collector along the thickness direction, obtaining a positive electrode active layer after drying, and pressing to obtain the positive electrode plate.
[0034] The present invention also provides a lithium-ion battery comprising a negative electrode plate, a separator and an electrolyte, and importantly, comprising the above recycled lithium battery positive electrode material or the above positive electrode plate.
[0035] Beneficial effects of the present invention:
[0036] The present invention uses a novel LNOC ternary molten salt method to remove impurities from waste LIBs in one step and separate the positive electrode material and the current collector, which has the advantages of low temperature, short time, environmental protection and high separation efficiency. It has been verified that when the mass ratio of LiNO3, LiOH and Li2CO3 is 3:2:0.45, the separation efficiency of the two reaches the best (99.95%). Compared with the common traditional high-temperature calcination method, it reduces toxic gas pollution and protects the environment; due to the protection of the passivation layer, the aluminum foil can also be directly recycled, eliminating the subsequent complex aluminum removal steps and increasing economic benefits; the separated positive electrode material exhibits good electrochemical properties, which are comparable to the performance of the primary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The weight changes of the systems in different embodiments at different temperatures.
[0038] Figure 2 The results of the cycle performance test. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0040] As described in the background technology, in the recycling process of waste lithium-ion batteries, especially the positive electrode material NCM, the separation of the positive electrode material and the foil is a major difficulty. One reason is that the incomplete removal of the binder on the positive electrode material and the foil will affect the purity of the recycled material and the electrochemical performance of the recycled material after it is prepared into a battery; another reason is that it is difficult to achieve efficient repair of the positive electrode material NCM, which will also affect the performance of the battery prepared from the recycled material to a certain extent.
[0041] Traditional binder recovery methods have toxic gas pollution, high energy consumption, low binder pretreatment separation efficiency, inability to eliminate in the pressureless cleaning system, high binder treatment conditions, and increased difficulty in subsequent extraction of metal elements. In order to overcome these problems, the present invention proposes a new method for removing binders from waste lithium batteries and separating positive electrode materials (nickel-cobalt-manganese ternary materials) and current collectors in one step using ternary molten salt. Specifically:
[0042] The present invention provides a method for recycling a lithium battery positive electrode material and a current collector, comprising the following steps:
[0043] S1. Discharge waste lithium-ion batteries (S-LIBs), disassemble and collect positive electrode sheets;
[0044] S2, mixing the positive electrode plate with the ternary molten salt material, heating to a preset temperature for heat treatment to separate the positive electrode material of the lithium battery and the current collector, and recovering the positive electrode material of the lithium battery and the current collector respectively;
[0045] The positive electrode material of the waste lithium-ion battery is a mixture of a nickel-cobalt-manganese ternary material and a conductive agent, the ternary molten salt material is composed of lithium nitrate, lithium hydroxide and lithium carbonate, and the mass ratio of the lithium nitrate, lithium hydroxide and lithium carbonate is 3: (1.5-2.5): (0.25-1); the preset temperature is greater than or equal to 200° C., and the heat treatment time is greater than 10 minutes.
[0046] In the nickel-cobalt-manganese ternary material, the molar ratio of Ni, Co and Mn is (8-9.5):(0.2-0.8):(0.2-0.8), and the sum of the molar ratios is 1.
[0047] In the prior art, most of them first use mechanical methods, ultrasonic methods, etc. to separate the positive electrode material in the positive electrode sheet from the current collector to obtain the positive electrode powder material, and then perform lithium replenishment operation for easy recycling. Unlike the prior art, the method described in the present invention does not contain a pretreatment process, and there is no need to separate the active material from the current collector first. Instead, the waste positive electrode sheet is directly treated with a ternary molten salt, and the separated foil and positive electrode material can be obtained after the treatment. The treatment process can not only remove the binder, but also the foil can be completely separated due to the protection of the oxide layer. More importantly, the positive active material (nickel-cobalt-manganese ternary material) is repaired by lithium replenishment in this process, which helps to maintain the electrochemical properties of the positive electrode material after recycling, truly realizing one-step recycling, simplifying the recycling process, and is more suitable for large-scale recycling in industry, and the recycling efficiency is comparable to the prior art.
[0048] In addition, the positive electrode material recovered in the present invention contains NCM material and conductive agent, that is, the method does not separate NCM powder separately, thereby eliminating the steps of conductive agent treatment and repeated addition of conductive agent during reuse. The selected molten salt system will not have an adverse effect on the conductive agent. The recovered NCM and conductive agent can be directly reused as a mixture, further reducing costs.
[0049] In summary, the method of the present invention has the unique characteristics of high efficiency, short time, low energy consumption and environmental protection. First, due to the protection of the passivation layer, the aluminum foil can also be directly recycled, eliminating the subsequent complicated aluminum removal steps and increasing economic benefits; secondly, the present invention removes impurities and separates the positive electrode material in one step, and the separated positive electrode material can be directly regenerated as a positive electrode material for lithium-ion batteries. This is an effective, economical and environmentally friendly sustainable process for recycling S-NCM.
[0050] In the present invention, the "molten salt" is a melt formed by melting lithium salts LiNO3, LiOH, and Li2CO3. The preparation method is: put the molten salt into a molten salt tank and heat it directly to melt it, or add a small amount of water to the molten salt and heat it to melt it. After it is melted to a viscosity sufficient to be circulated by a molten salt pump, it is sent to a heat-carrying furnace to gradually circulate and heat it until it reaches the desired molten state.
[0051] The recycling method of the present invention is proposed for NCM positive electrode materials, wherein the ternary molten salt is a mixed molten salt, that is, three different lithium salts are used as reactants to participate in the chemical reaction and act as a flux, playing the role of a liquid medium. + and anion NO3 - 、CO3 2- OH - Composition, there are electrostatic forces, short-range repulsion, van der Waals forces and other interaction forces between ions. The molten state accelerates the ion transfer speed, and it may be due to the synergistic cooperation between these three specific anions, which promotes the decomposition of the binder and provides support for the crystal structure of NCM. In the process, the molten salt system replenishes lithium while evaporating gas, avoiding the introduction of impurities. It has been verified that when the mass ratio of LiNO3, LiOH and Li2CO3 is 3:2:0.45, and the mass ratio of waste positive electrode sheet to ternary molten salt is 1:2, the separation efficiency of the two reaches the best.
[0052] Preferably, the steps are as follows:
[0053] (1) discharging the waste lithium-ion battery, disassembling the battery cell, and obtaining the positive electrode sheet and the negative electrode sheet;
[0054] (2) removing the residual electrolyte and collecting the positive electrode sheet;
[0055] (3) The positive electrode sheet and the ternary molten salt material are mixed in proportion and heated to 350-500° C. at a rate of 2-6° C. / min in an air atmosphere for heat treatment for 10-30 minutes. After the system is cooled, the lithium battery positive electrode material and the current collector are recovered separately.
[0056] In the embodiment of the present invention, taking aluminum foil and NCM9055 as materials to be recycled as an example, the steps are as follows:
[0057] 1. Discharge the spent lithium-ion batteries in 5-20% NaCl solution for 45-60 hours, and then disassemble them by physical methods in a fume hood.
[0058] 2. Immediately after taking out, rinse the obtained positive electrode sheet and negative electrode sheet with dimethyl carbonate 2-3 times to remove the residual electrolyte.
[0059] 3. Select LiNO3, LiOH, and Li2CO3 (LNOC) and mix these three materials into a ternary molten salt material in a mass ratio of 3: (1.5-2.5): (0.25-1), select LiNi0.9CO0.05Mn0.05O2 (NCM9055) as the positive electrode material, and select 9 series positive electrode sheets as experimental objects. For the convenience of subsequent tests, select five batteries from the same batch as experimental objects to ensure the uniformity of the weight of the aluminum foil.
[0060] 4. Cut the disassembled positive electrode sheet into 100*100mm blocks (B-NCM), put the B-NCM into a ceramic crucible cabinet, and mix it evenly with the ternary molten salt (LNOC) at a mass ratio of salt to positive electrode sheet of 10:1, 5:1, 2:1, and 1:1 respectively. The working temperature is set at 350-500℃ for 10-30 minutes. All experiments are heated at a rate of 2-6℃ / min in an air atmosphere.
[0061] 5. Cool the electrode naturally to room temperature (25°C, and introduce the tail gas of the entire separation process into an alkaline solution to absorb the fluoride gas released during the treatment process).
[0062] 6. Afterwards, the separated aluminum foil (S–Al) and the separated spent cathode material (S-NCM) were washed and dried.
[0063] In step 3, LiNO3, LiOH, and Li2CO3 in the ternary molten salt material are mixed in a mass ratio of 3: (1.5-2.5): (0.25-1), for example, 3:1.5:0.25, 3:1.5:0.5, 3:1.5:0.75, 3:1.5:1, 3:2:0.25, 3:2:0.3, 3:2:0.35, 3:2:0.4, 3:2:0.45, 3:2:0. :2:0.5, 3:2:0.55, 3:2:0.6, 3:2:0.65, 3:2:0.7, 3:2:0.75, 3:2:0.8, 3:2:0.85, 3:2:0.9, 3:2:0.95, 3:2:1, 3:2.5:0.25, 3:2.5:0.5, 3:2.5:0.75, 3:2.5:1, etc., including but not limited to the ratios listed above. In the present invention, the best mixing ratio is screened out according to the separation efficiency and the electrical properties of the recycled material based on the specific positive electrode material NCM9055, that is, 3:2:0.45, 3:2:0.25, 3:2:0.75 and 3:2:1 are next.
[0064] In step 4, the mass ratio of the ternary molten salt material to the positive electrode plate is (1-10):1. For example, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, etc., including but not limited to the ratios listed above. Among them, the optimal ratio is determined to be 2:1 through screening.
[0065] In step 4, the heating temperature may be 200-500°C, such as 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, preferably 350-500°C, such as 401°C, 402°C, 403°C, 404°C, 405°C, 406°C, 407°C, 408°C, 409°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C, 500°C, etc., including but not limited to the temperatures listed above. Among them, 406°C is most preferred.
[0066] In step 4, the heating time is 10-30 min, such as 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc., including but not limited to the time lengths listed above, and 15 min is most preferred.
[0067] In step 4, the heating rate is 2-6°C / min, such as 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, etc., including but not limited to the rates listed above. Among them, 3°C / min is most preferred.
[0068] There are two main reasons for the degradation of positive electrode materials: one is the loss of lithium: the lithium existing in the positive electrode material cannot be completely returned to the positive electrode during the cycle of the battery, resulting in reduced battery performance. The second is surface phase change: the surface of the material in contact with the electrolyte is more prone to phase change, from the original layered structure to the spinel phase and salt rock phase. These two structures have lower lithium ion conductivity, which increases polarization and performance degradation. When using the molten salt method to replenish lithium in order to restore electrical properties, the material is first replenished with lithium, and then sintered to achieve the ideal phase structure. Among them,
[0069] The mixing ratio of ternary molten salt and positive electrode plate affects the separation efficiency and electrical properties of recycled materials, which may be related to the degree of lithium replenishment and the introduction of excess impurities. When the ratio of ternary molten salt to positive electrode plate is higher than 10:1 or lower than 1:1, the separation efficiency decreases and the capacity of the constructed battery also deteriorates significantly.
[0070] The introduction of the molten salt system reduces the reaction temperature, accelerates the reaction rate, and improves the crystal structure and performance of the material to be recycled. Determination of the lithium replenishment reaction temperature and reaction time: (1) The lithium replenishment temperature was determined by TG-DSC. Specifically, the weight loss in the first section of the TG curve belongs to the loss of crystal water in the LiOH lithium salt. Then, the weight loss in the second stage belongs to the dissolution of the molten salt. It can be seen that the actual eutectic point of the ternary molten salt is about 150-200℃. The third stage of weight loss occurs between 200-350℃ and belongs to the decomposition of the molten salt. The lithium salt reacts with the attenuated positive electrode material to replenish lithium for it and release NO2, CO2 and H2O gas. (2) The lithium replenishment temperature and time are determined by the recovery of chemical composition and surface crystal structure. Comparing the attenuated material with the regenerated material, the loss of lithium in the attenuated material can be seen in the X-ray diffraction diagram, while the regenerated material shows that the lithium content has recovered to varying degrees, and the best recovery is to the original value, proving that lithium has been successfully replenished into the attenuated positive electrode material. At the same time, the salt rock phase structure of the attenuated material and the regenerated material is compared. The strength curve along the lithium layer on the surface of the attenuated material shows a significant increase in surface strength. This phenomenon is caused by the migration of transition metal elements to the lithium layer, proving that a phase change has occurred on the surface of the material. However, the presence of salt rock phase and transition metal elements in the lithium layer was not observed on the surface of the regenerated material, indicating that the regeneration process can restore the salt rock phase to the original layered structure of the material and achieve the recovery of the surface crystal structure. The above characterization shows that when the material is NCM9055, the optimal temperature is 406°C, the optimal time is 15 minutes, and the heating rate is 3°C / min.
[0071] Recovery of electrochemical performance: After 15 minutes of molten salt lithium replenishment reaction, the capacity and cycle performance of the recycled material are completely restored to the performance of the original material. When it is less than 10 minutes, the lithium replenishment reaction time is too short and the reaction is not complete, so all indicators are lower than the original material. When it exceeds 30 minutes, the heating will affect the crystal structure and its stability to a certain extent, so the electrochemical performance indicators are slightly lower than that of 15 minutes.
[0072] In step 4, the waste positive electrode sheets are cut into units of 100*100 mm or even smaller, so as to increase the surface area in contact with the ternary molten salt during the mixing process, thereby fully mixing with the ternary molten salt and improving the lithium replenishment efficiency.
[0073] After step 6, the step of crushing S-NCM is also included to obtain a usable positive electrode material. Specifically, S-NCM is crushed into particles with D50 = 1-10 μm, preferably 4-8 μm. The particle size of the active material will directly affect the charge and discharge behavior of the lithium battery, and will affect the rheological properties of the battery slurry, and the rheological properties will directly affect the coating and processing stability of the slurry. Among them, the crushing is preferably air flow crushing, preferably with an air flow velocity of 5-20 m / s, an agitator speed of 500-3000 rpm, and a temperature of 20-25°C.
[0074] The present invention also provides a positive electrode plate prepared using the above recycled materials, comprising a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer comprises the above recycled lithium battery positive electrode material (including a conductive agent) and a binder.
[0075] Preferably, the positive electrode active layer comprises the following components by mass percentage: 85-95% of lithium battery positive electrode material and 5-15% of binder, that is, 75-95% of NCM material, 5-15% of conductive agent and 5-15% of binder.
[0076] Preferably, the conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0077] Preferably, the binder is a binder well known to those skilled in the art, without any particular limitation, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF is selected.
[0078] Preferably, the thickness of the positive electrode active layer is in the range of 100-300 μm, for example, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, etc., including but not limited to the thickness values listed above.
[0079] The embodiment of the present invention also provides a method for preparing the positive electrode sheet as described above, comprising the following steps:
[0080] S01, preparing a positive electrode active slurry by mixing a formulated amount of positive electrode material and a binder;
[0081] S02, coating the positive electrode active slurry on at least one side of the current collector along the thickness direction, obtaining a positive electrode active layer after drying, and pressing to obtain the positive electrode plate.
[0082] Preferably, the current collector is aluminum foil, or other materials that can be used as a current collector; preferably, the thickness of the current collector is in the range of 5-14 μm.
[0083] The embodiments of the present invention also provide a lithium-ion battery comprising a negative electrode plate, a separator and an electrolyte, and more importantly, the positive electrode plate.
[0084] Preferably, the negative electrode plate comprises a negative electrode active layer; the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder.
[0085] Preferably, the negative electrode active layer comprises the following components in mass percentage: 75-95% of negative electrode active material, 5-15% of conductive agent and 5-15% of binder.
[0086] Preferably, the negative electrode active material is selected from one or more of artificial graphite, natural graphite, silicon, silicon oxide, titanium phosphorus oxide (including sodium titanium phosphate, sodium titanium manganese phosphate, titanium phosphate).
[0087] Preferably, the conductive agent is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0088] Preferably, the binder is a negative electrode binder well known to those skilled in the art without any particular limitation, such as one or more of chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer.
[0089] Preferably, the type of the diaphragm is any diaphragm well known to those skilled in the art without any particular limitation, such as one or more of polyethylene, polypropylene, polyacrylonitrile, polyacrylonitrile fiber, polyamic acid, polyimide, polyamide, polydopamine, polyarylethersulfone, polyvinylidene fluoride, polyethylene oxide, polyethylene terephthalate, polyester, non-woven fabric membrane and cellulose paper-based isolation membrane.
[0090] Preferably, the electrolyte is an electrolyte well known to those skilled in the art without any special restrictions, the solvent is at least one of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether; the electrolyte salt is at least one of sodium perchlorate, sodium bis(oxalate)borate, and sodium hexafluorophosphate.
[0091] Example 1
[0092] A method for recycling waste lithium-ion battery positive electrode materials comprises the following steps:
[0093] (1) Pretreatment of waste LiNi0.9CO0.05Mn0.05O2 (NCM9055) positive electrode materials: The used lithium-ion batteries (binder: PVDF) were discharged in 15% NaCl solution for 48 hours and then disassembled by physical methods in a fume hood. Immediately after removal, the obtained positive and negative electrode sheets were rinsed three times with dimethyl carbonate to remove residual electrolyte.
[0094] (2) Preparation of LiNO3, LiOH, Li2CO3 (LNOC) ternary eutectic molten salt: LiNO3, LiOH, Li2CO3 are mixed in a mass ratio of 3:2:0.25 and prepared into a ternary molten salt material.
[0095] (3) The disassembled positive electrode sheet of (1) was cut into 100*100 mm blocks (B-NCM), and the B-NCM was placed in a ceramic crucible cabinet and uniformly mixed with ternary molten salt (LNOC) at a mass ratio of salt to B-NCM of 2:1. The working temperature was set at 406 °C for 15 minutes. All experiments were heated at a rate of 3 °C / min in an air atmosphere and TG tests were performed.
[0096] (4) The electrode is naturally cooled to room temperature (25°C) and the tail gas of the entire separation process is introduced into a CaO-rich solution to absorb the fluoride gas released during the treatment process.
[0097] (5) Afterwards, the separated aluminum foil (S–Al) and the separated spent cathode material (S-NCM) were washed, dried, and weighed.
[0098] Example 2
[0099] A method for recycling waste lithium-ion battery positive electrode materials, except for step (2): LiNO3, LiOH, and Li2CO3 (LNOC) are mixed in a mass ratio of 3:2:0.45 to prepare a ternary molten salt material; the other steps are the same as those in Example 1.
[0100] Example 3
[0101] A method for recycling waste lithium-ion battery positive electrode materials, except for step (2): LiNO3, LiOH, and Li2CO3 (LNOC) are mixed in a mass ratio of 3:2:0.75 to prepare a ternary molten salt material; the other steps are the same as those in Example 1.
[0102] Example 4
[0103] A method for recycling waste lithium-ion battery positive electrode materials, except for step (2): LiNO3, LiOH, and Li2CO3 (LNOC) are mixed in a mass ratio of 3:2:1 to prepare a ternary molten salt material; the other steps are the same as those in Example 1.
[0104] Example 5
[0105] A method for recycling waste lithium-ion battery positive electrode materials, except step (3): the working temperature is 500° C.; the other steps are the same as those in Example 2.
[0106] Example 6
[0107] A method for recycling waste lithium-ion battery positive electrode materials, except for step (3): the working temperature is 350° C.; the other steps are the same as those in Example 2.
[0108] Example 7
[0109] A method for recycling positive electrode materials of waste lithium-ion batteries, except that step (3) comprises a working time of 10 minutes; the other steps are the same as those of Example 2.
[0110] Example 8
[0111] A method for recycling positive electrode materials of waste lithium-ion batteries, except that step (3) is performed for 30 minutes; other steps are the same as those in Example 2.
[0112] Example 9
[0113] The waste LiNi0.9CO0.05Mn0.05O2 (NCM9055) positive electrode material was replaced with the waste LiNi0.88CO0.06Mn0.06O2 (NCM8866) positive electrode material, and the remaining steps were the same as in Example 2.
[0114] Comparative Example 1
[0115] 1) Soak the positive electrode waste sheets in water, with the mass ratio of the positive electrode waste sheets to water being 1:3-4;
[0116] 2) Then stir to make the positive electrode material fall off the electrode sheet;
[0117] 3) dispersing the fallen positive electrode material to obtain positive electrode material slurry, and then separating the positive electrode material slurry from the aluminum foil;
[0118] 4) Evaporate the water in the positive electrode material slurry to obtain the product.
[0119] Comparative Example 2
[0120] Adjust the ternary molten salt system, add a lithium salt, and the remaining steps are the same as Example 2: prepare LiNO3, LiOH, Li2CO3, LiCl quaternary eutectic molten salt: these 4 materials are mixed into a molten salt material in a mass ratio of 3:2:0.45:1; the other steps are the same as Example 2.
[0121] Comparative Example 3
[0122] Adjust the ternary molten salt system, and the remaining steps are the same as in Example 2: prepare LiCl, LiOH, and Li2CO3 ternary eutectic molten salt, and these three materials are mixed into a molten salt material in a mass ratio of 3:2:0.45; the other steps are the same as in Example 2.
[0123] Comparative Example 4
[0124] Adjust the ternary molten salt system, and the remaining steps are the same as in Example 2: prepare CH3COOLi, LiOH, and Li2CO3 ternary eutectic molten salt, and these three materials are mixed into a molten salt material in a mass ratio of 3:2:0.45; the other steps are the same as in Example 2.
[0125] Comparative Example 5
[0126] Adjust the ternary molten salt system, and the remaining steps are the same as in Example 2: prepare Li2SO4, LiOH, and Li2CO3 ternary eutectic molten salt, and these three materials are mixed into a molten salt material in a mass ratio of 3:2:0.45; the other steps are the same as in Example 2.
[0127] Comparative Example 6
[0128] The mass ratio of the ternary molten salt material to the positive electrode plate is adjusted to 15:1, and the rest is the same as in Example 2.
[0129] Comparative Example 7
[0130] The mass ratio of the ternary molten salt material to the positive electrode plate is adjusted to 0.5:1, and the rest is the same as in Example 2.
[0131] Comparative Example 8
[0132] The working time of step (3) was adjusted to 60 min, and the rest was the same as in Example 2.
[0133] Test Case
[0134] Lithium-ion batteries were constructed using the waste positive electrode materials (S-NCM) separated in the above embodiments and comparative examples, and the electrical properties of each battery were tested.
[0135] 1. Preparation of lithium-ion batteries
[0136] Assembly of the battery: The positive electrode is prepared by a slurry of 96wt% of the positive electrode material prepared in the embodiment and the comparative example (containing 4wt% acetylene black) and 6wt% polyvinylidene fluoride (PVDF) binder. The obtained slurry is coated on aluminum foil. After drying and rolling, the obtained positive electrode sheet is punched to obtain a disc with a diameter of 1.2cm. The items required for the experiment are placed in an oven at 60°C for 12h of drying. Subsequently, a CR2032 button battery is assembled in an argon-protected glove box, in which the negative electrode is a purchased metal lithium sheet, and the electrolyte is a mixed solution of 1mol / L LiPF6 dissolved in ethylene carbonate (EC) / dimethyl carbonate (DEC) / ethyl methyl carbonate (EMC) (volume ratio of 1:1:1). The battery assembly order is negative electrode shell-metal lithium-diaphragm-positive electrode sheet-gasket-spring-positive electrode shell.
[0137] 2. Performance Test
[0138] (1) Separation efficiency:
[0139] In the present invention, the separation efficiency is calculated by the formula: η(%) = (W1 / W2) × 100%, W1 is the weight of the positive electrode sheet minus the weight of the aluminum foil, and W2 is the recovered NCM.
[0140] Table 1
[0141]
[0142]
[0143] (2)TG-DSC test:
[0144] The reaction temperature of S-NCM and ternary molten salt was set in the range of 0-400°C by TG-DSC test (Netzsch STA449C) at a heating rate of 5°C / min and in nitrogen. The specific test operation is as follows:
[0145] ① Sample preparation: Select appropriate samples and perform pretreatment as needed, including grinding, screening or drying. Ensure that the quality and purity of the samples meet the experimental requirements.
[0146] ②Instrument setup: Set up the TG-DSC instrument according to the experimental requirements. This includes calibrating the thermocouple, weighing the sample and reference, and setting parameters such as heating / cooling rates. Make sure the instrument is working properly and ready for the experiment.
[0147] ③ Sample loading: Place the prepared samples on the sample tray or sample table. Determine the mass range and quantity of the samples according to the experimental requirements to ensure uniform distribution and proper loading of the samples.
[0148] ④ Clear the instrument: Before conducting the experiment, make sure that the ambient gas or atmosphere in the instrument matches the experimental requirements. You can use inert gas (nitrogen) to clear the instrument to ensure the purity of the experimental environment.
[0149] ⑤ Experimental operation: Start the experimental operation and change the temperature according to the set temperature rise program (5℃ / min). During the whole experiment, record and monitor the mass change and thermal response of the sample. At the same time, record the ambient temperature and the thermal response of the reference as a benchmark.
[0150] Results Figure 1 It can be seen that the weight change of Example 2 is the largest, from which it can be preliminarily judged that the proportion of Example 2 is more conducive to the decomposition of the material.
[0151] The optimal ternary molten salt system of LNOC with different mass ratios was determined by TG-DSC. The weight loss in the first section of the TG curve belongs to the loss of crystal water in the LiOH·H2O lithium salt. Then, the weight loss in the second stage belongs to the dissolution of the molten salt. It can be seen that the actual eutectic point of the ternary molten salt is about 150-200℃. The third stage of weight loss occurs between 200-350℃ and belongs to the decomposition of the molten salt, releasing NO2, CO2 and H2O gases. The reaction formula is as follows:
[0152] LiOH·H2O→LiOH+H2O (1)
[0153] LiOH→Li2O+H2O (2)
[0154] LiNO3→NO2+Li2O (3)
[0155] Li2CO3→CO2+Li2O (4)
[0156] (3) Power-off test:
[0157] Test conditions: LR 2032, 0.1C, 2.5~4.3V, vs. Li+ / Li,
[0158] 0.1C charging capacity: 0.1C constant current charging to 4.0V, 4.0V constant voltage charging to a cut-off current of 0.05C, standing for 5 minutes. The capacity measured in this step is the 0.1C charging capacity (denoted as C0).
[0159] 0.1C discharge capacity: 0.1C constant current discharge to 2.8V, let stand for 5 minutes. The capacity measured in this step is the 0.1C discharge capacity (recorded as C1).
[0160] The first coulomb efficiency (first efficiency) is: C1 / C0. The charging and discharging equipment used is a blue electric charging and discharging instrument.
[0161] The results are shown in Table 2.
[0162] Table 2
[0163]
[0164]
[0165] (4) Cyclic performance test:
[0166] Test process: Place the battery in a 45°C environment, charge it to 4.35V with a current of 1C, then charge it to 0.05C with a constant voltage, let it stand for 30 minutes, then discharge it to 2.8V with a current of 1C, let it stand for 30 minutes. Repeat the above charge and discharge process until the battery capacity is less than 80% of the initial capacity or the test is stopped after 1500 cycles. See the results Figure 2 The thick lines are the long cycle data of the battery of Example 2, and the thin lines are the long cycle data of the battery of Comparative Example 1. It can be seen that the cycle performance of the battery prepared by the material obtained in Example 2 is much better than that of Comparative Example 1.
[0167] In summary, the separation efficiency of the embodiment is basically maintained between 97% and 99.95%, indicating that the separation effect is good. The separation efficiency of all comparative examples is higher than 100%, indicating that the impurities are not completely removed, which may affect the performance of the battery prepared from the recycled materials to a certain extent. The buckle test results show that the battery prepared from the recycled materials in Example 2 has the best performance, which is basically close to the newly prepared positive electrode material. The battery performance prepared from the recycled materials in the other embodiments is comparable to that of the newly prepared positive electrode material, while the discharge capacity and first efficiency of the comparative examples are significantly worse than those in the embodiment, proving the excellent synergistic effect of the specific molten salt system selected by the present invention in the NCM ternary material recycling process.
[0168] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for recycling positive electrode materials of lithium batteries, characterized in that: The following steps are involved: S1. Discharge the waste lithium-ion batteries, disassemble and collect the positive electrode sheets; S2, mixing the positive electrode plate with the ternary molten salt material, heating to a preset temperature for heat treatment to separate the positive electrode material of the lithium battery and the current collector, and recovering the positive electrode material of the lithium battery; The lithium battery positive electrode material comprises a nickel-cobalt-manganese ternary material, the ternary molten salt material consists of lithium nitrate, lithium hydroxide and lithium carbonate, and the mass ratio of the lithium nitrate, lithium hydroxide and lithium carbonate is 3:(1.5-2.5):(0.25-1); the preset temperature is greater than or equal to 200°C, and the heat treatment time is greater than or equal to 10 minutes.
2. The recycling method according to claim 1, characterized in that: In the nickel-cobalt-manganese ternary material, the molar ratio of Ni, Co and Mn is (8-9.5):(0.2-0.8):(0.2-0.8).
3. The recycling method according to claim 1, characterized in that: In step S2, at least one of the following features is included: (1) The preset temperature is 350-500°C; (2) The heating rate is 2-6°C / min; (3) The heat treatment time is 10-30 minutes.
4. The recycling method according to claim 1, characterized in that: In step S2, the mass ratio of the ternary molten salt material to the positive electrode plate is (1-10):
1.
5. The recycling method according to claim 1, characterized in that: The positive electrode material of the lithium battery is a mixture of a nickel-cobalt-manganese ternary material and a conductive agent; Preferably, in the lithium battery positive electrode material, the mass percentages of the nickel-cobalt-manganese ternary material and the conductive agent are: 75-95% of the nickel-cobalt-manganese ternary material and 5-15% of the conductive agent; Preferably, the conductive agent is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
6. The recycling method according to claim 1, characterized in that: The step S2 also includes a waste gas treatment step; the waste gas treatment is: passing the waste gas into an alkaline solution.
7. The recycling method according to claim 1, characterized in that: In the step S2, after the lithium battery positive electrode material and the current collector are separated, the lithium battery positive electrode material and / or the current collector are washed and dried to recover the lithium battery positive electrode material and / or the current collector.
8. The recycling method according to claim 7, characterized in that: After washing and drying the positive electrode material of the lithium battery, the step of crushing the positive electrode material of the lithium battery is included.
9. The recycling method according to claim 8, characterized in that: Contains at least one of the following characteristics: (1) The pulverizing method includes air flow pulverizing; (2) The particle size D50 of the lithium battery positive electrode material after crushing is 1-10 μm.
10. A lithium ion battery, characterized in that: The lithium-ion battery contains the lithium battery positive electrode material obtained by the recovery method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Fused salt activation regeneration method for waste lithium ion battery anode material lithium cobalt oxide
CN110217830A
Fused salt regeneration activation method for waste lithium ion battery ternary positive pole material
CN110233305A
Method for preparing {010} crystal face exposed flaky single- crystal ternary electrode material by regenerating a waste lithium ion battery
CN113265704A
Direct repair method for waste ternary lithium battery positive electrode material and ternary positive electrode material prepared by direct repair method
CN114204013A
Method for directly regenerating NCM positive electrode by using ternary molten salt, regenerated NCM positive electrode active material and application of regenerated NCM positive electrode active material
CN117855657A